Stability over time of the level of maximal lipid oxidation during exercise - Brun, J.-F.; Romain, A.-J.; Guiraudou, M.; Fédou, C.; Mercier, J. (Science & Sports, 2014)
Introduction: The level of maximal lipid oxidation at exercise (LIPOXmax or FATmax) is exercise intensity, variable among individuals, at which a steady-state exercise performed over 45-60 minutes uses the greatest lipid/carbohydrate ratio and thus, minimises carbohydrate waste. This level has been demonstrated to be highly reproducible if tested in standardised conditions and is modified by a host of physiological or pathological situations. Whether it is stable over long periods of time remained unknown. Methods: We had the possibility to measure this stability in a database of 1600 exercise calorimetries performed in our unit since 1998 and including several patients that did not modify their exercise or eating habits and were re-tested after a mean interval of 30 months. Patients (n = 11) represented a wide range of age (28-74 years), body mass index (22 to 46.7 kg/m2) and aerobic capacity. Results: Their LIPOXmax ranged between a power of 18 to 123 watts and their maximal fat oxidation rate (MFO) ranged between 75 and 423 mg/min. There was a remarkable stability of the LIPOXmax expressed in crude power (r = 0.993, P < 0.001; Bland Altman plots: mean difference -2.36, CI: [-3.33 to 8.06]. MFO was less reproducible over those long periods of time (r = 0.694, P < 0.02; mean difference 4, CI: [-53 to 61]). Conclusion: Therefore, the power at which lipid oxidation reaches a maximal during exercise remains stable over a mean period of 30 months if diet and exercise habits are not modified.